2005
DOI: 10.1177/154193120504901732
|View full text |Cite
|
Sign up to set email alerts
|

Compressed File Length Predicts Search Time and Errors on Visual Displays

Abstract: Search times and errors were recorded for targets (a triangle or trapezoid) in marine radar, chart, and radar-chart overlay bitmap computer displays. Lossless JPEG and ZIP compressed file lengths were obtained for each display. The two types of file length were correlated and they predicted both the maximum time to search each display and the number of errors made per search. Compressed file length is analogous to algorithmic complexity, a theoretical measure of bit string complexity. It predicts both subjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In terms of hit rate, the integration of buildings (level 3), as currently recommended by public authorities [73], improves object-location memory, most likely due to anchor effects of reference nodes in urban topographies [51]. Of note is that this result, at first glance, seems to contradict cognitive load theory and assumptions that complex, heavily urbanised maps would entail greater need for spatial orientation [60]; see also [54], [56] and more recognition errors in case of increasing visual complexity [53], [74]. An explanation for these diverging findings is provided by the ‘levels of processing’ [88], where it has been proven that a higher demand during memory encoding leads to better memory performance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In terms of hit rate, the integration of buildings (level 3), as currently recommended by public authorities [73], improves object-location memory, most likely due to anchor effects of reference nodes in urban topographies [51]. Of note is that this result, at first glance, seems to contradict cognitive load theory and assumptions that complex, heavily urbanised maps would entail greater need for spatial orientation [60]; see also [54], [56] and more recognition errors in case of increasing visual complexity [53], [74]. An explanation for these diverging findings is provided by the ‘levels of processing’ [88], where it has been proven that a higher demand during memory encoding leads to better memory performance.…”
Section: Discussionmentioning
confidence: 96%
“…The identified numbers of distinct objects characterising LANDSCAPE was double-checked with ArcMap 10.1, the main component of Esri's ArcGIS suite of geospatial processing programs. Alternatively, map complexity can be determined by lossless JPEG compressed file lengths [52], [74]. On average, the following jpg file sizes were obtained: 1,036 kb (highly rural), 1,564 kb (rural), 1,784 kb (rural-suburban), 2,552 kb (urban) and 4,261 kb (highly urban).…”
Section: Methodsmentioning
confidence: 99%
“…Complexity was determined using the size of each image in jpeg (compressed) format (Calvo and Lang, 2004). In previous research, compressed image file sizes have been shown to be highly correlated with both subjective measures of complexity (Donderi, 2006; Tuch et al, 2009) and objective visual search performance (Donderi and McFadden, 2005). …”
Section: Methodsmentioning
confidence: 94%
“…Importantly, these measures were not developed by computer scientists to predict subjective complexity in the first place, but were only currently successfully applied to various types of visual stimuli by psychologists. The ratio between the original and the compressed file sizes of marine electronic charts and radar images [101,105], icons [103], line drawings [99,103] environmental scenes [74,104] and a wide range of artistic works [74] have been shown to be positively correlated with ratings of subjective complexity. It needs to be stated plainly that these types of stimuli were not selected within the context of a specific emotion model.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we extended this set of measures by including several potentially new measures of objective complexity, such as PNG (Portable Network Graphics) and TIFF (Tagged Image File Format) compression formats, measures of edge detection based on phase congruency [123], and the entropy of the image intensity histogram of a grayscale image [124]. It is also important to note that since it was already demonstrated earlier that compression file size is an indicator of subjective complexity [74,105], we selected pictures in JPEG format rather than uncompressed pictures as a starting point for all further transformations and analyses. This approach extends the implications and applicability of the current research findings since JPEG pictures are more easily accessible to the research community compared to (scans of) pictures in uncompressed formats.…”
Section: Introductionmentioning
confidence: 99%